Hepatocyte nuclear factor‐1β shapes the energetic homeostasis of kidney tubule cells. Issue 11 (15th October 2021) - Piedrafita, Alexis; Balayssac, Stéphane; Casemayou, Audrey; Saulnier‐Blache, Jean‐Sébastien; Lucas, Alexandre; Iacovoni, Jason S.; Breuil, Benjamin; Chauveau, Dominique; Decramer, Stéphane; Malet‐Martino, Myriam; Schanstra, Joost P.; Faguer, Stanislas
Abstract: Energetic metabolism controls key steps of kidney development, homeostasis, and epithelial repair following acute kidney injury (AKI). Hepatocyte nuclear factor‐1β (HNF‐1β) is a master transcription factor that controls mitochondrial function in proximal tubule (PT) cells. Patients with HNF1B pathogenic variant display a wide range of kidney developmental abnormalities and progressive kidney fibrosis. Characterizing the metabolic changes in PT cells with HNF‐1β deficiency may help to identify new targetable molecular hubs involved in HNF1B ‐related kidney phenotypes and AKI. Here, we combined 1 H‐NMR‐based metabolomic analysis in a murine PT cell line with CrispR/Cas9‐induced Hnf1b invalidation ( Hnf1b −/− ), clustering analysis, targeted metabolic assays, and datamining of published RNA‐seq and ChIP‐seq dataset to identify the role of HNF‐1β in metabolism. Hnf1b −/− cells grown in normoxic conditions display intracellular ATP depletion, increased cytosolic lactate concentration, increased lipid droplet content, failure to use pyruvate for energetic purposes, increased levels of tricarboxylic acid (TCA) cycle intermediates and oxidized glutathione, and a reduction of TCA cycle byproducts, all features consistent with mitochondrial dysfunction and an irreversible switch toward glycolysis. Unsupervised clustering analysis showed that Hnf1b −/− cells mimic a hypoxic signature and that they cannot furthermore increase glycolysis‐dependent energetic supply during hypoxic challenge. Metabolome analysis also showed alteration of phospholipid biosynthesis in Hnf1b −/− cells leading to the identification of Chka, the gene coding for choline kinase α, as a new putative target of HNF‐1β. HNF‐1β shapes the energetic metabolism of PT cells and HNF1B deficiency in patients could lead to a hypoxia‐like metabolic state precluding further adaptation to ATP depletion following AKI.